The effect of scenes of violence in television on reinforcing the aggressive behavior of the child: A reading of the effects and Perception of prevention mechanisms - Talla , Lamia (Social Empowerment Journal, 2020)
The media play a dangerous role in inciting the child to violence, especially television and what is shown of thriller and horror films as well as dangerous or violent sports as well as cartoons that encourage violence and bloodshed, as children tend to imitate the characters of these films and cartoons, and thus affect their minds Which was confirmed by many studies that there is a strong positive correlation between watching violent television programs and aggressive behavior. On the other hand, it is the duty of society towards the violence in the media to carry out the task of censoring what is presented in the various media, holding those responsible for the dissemination and circulation of these scenes through the enactment of laws criminalizing such acts, and also the development of an ethical system that preserves the morals of the society, and maintains its customs and traditions against This negative phenomenon, including the education of generations to renounce that image of violence and unacceptability in any case, and the manufacture of public awareness rejecting them.